2001
DOI: 10.1523/jneurosci.21-10-03429.2001
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Control of BK Potassium Channel Function and Intrinsic Firing Properties of Adrenal Chromaffin Cells

Abstract: The discovery that the hypothalamic-pituitary-adrenocortical (HPA) endocrine stress axis controls an alternative splicing decision in chromaffin Slo-encoded BK (big potassium) channels raised the possibility that activation of the HPA could serve as a mechanism to tune the intrinsic electrical properties of epinephrine-secreting adrenal chromaffin cells. To test this, we compared BK functional properties and cell excitability in chromaffin cells from normal and hypophysectomized (pituitaryablated) rats. Hypoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 53 publications
2
66
0
1
Order By: Relevance
“…Certainly, in some preparations, increased BK channel activity reduces neural excitability (19,20). However, BK channel activity has long been positively correlated with neural excitability (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, in some preparations, increased BK channel activity reduces neural excitability (19,20). However, BK channel activity has long been positively correlated with neural excitability (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…The e21(STREX) insert is highly conserved across vertebrates, at the amino acid level, suggesting it plays a common functional role, perhaps in the maintenance of high frequency or duration of action potentials (11,20). To date, a homologous e21(STREX) variant in invertebrate species (such as Drosophila or Caenorhabditis elegans) has not been identified; thus e21(STREX) likely represents a vertebrate specialization.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, BK channels have been shown to increase, rather than decrease, AP frequency (Brenner et al 2005;Gu et al 2007;Jaffe et al 2011;Lovell and McCobb 2001;MartinezEspinosa et al 2014;Montgomery et al 2012;Shruti et al 2008). Given that BK channels are activated by specific calcium sources, this suggests that some calcium channels' effects on excitability may be partly mediated by activation of proexcitatory BK channels.…”
Section: Given Their Broad Expression These Findings May Be Relevantmentioning
confidence: 99%